A review of studies on using nanofluids in flat-plate solar collectors - Sarsam, W.S.; Kazi, S.N.; Badarudin, A. (Elsevier, 2015)
Continuous escalation of the cost of generating energy is preceded by the fact of scary depletion of the energy reserve of the fossil fuels and pollution of the environment as developed and developing countries burn these fuels. To meet the challenge of the impending energy crisis, renewable energy has been growing rapidly in the last decade. Among the renewable energy sources, solar energy is the most extensively available energy, has the least effect on the environment, and is very efficient in terms of energy conversion. Thus, solar energy has become one of the preferred sources of renewable energy. Flat-plate solar collectors are one of the extensively-used and well-known types of solar collectors. However, the effectiveness of the collector's absorber plate to absorb solar energy limits the efficiency of this type of collector, as does the inefficient transfer of the solar energy via heat transfer to the fluid in the collector's flow channels. To improve its efficiency and performance, ``nanofluids,'' synthesized by mixing solid, nanometer-sized particles at low concentrations with the base fluid, have been used with remarkable effects on the thermophysical properties, such as thermal conductivity. The use of nanofluids as an advanced kind of fluids is a comparatively recent development. In this paper, the previous investigations of the performance of flat-plate solar collectors using nanofluids as working fluids are covered in detail. Then, some conclusions and recommendations are presented concerning the use of nanofluids in flat-plate solar collectors. (C) 2015 Elsevier Ltd. All rights reserved.